Aplikasi Pupuk Organik Cair pada Media Campuran Pupuk Kandang Sapi di Pertanaman Bawang Merah secara Terapung - Irmawati Irmawati; Susilawati Susilawati; Sri Sukarmi; Muhammad Ammar; Teguh Achadi; Azizul Amri (Seminar Nasional Lahan Suboptimal, 2021)
Irmawati I, Susilawat S, Sukarmi S, Ammar M, Achadi T, Amri A. 2021. Application of liquid organic fertilizer on shallot planted on cow manure mixture media in floating system. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang  20 Oktober 2021. pp. 713-720.  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Floating agriculture is an alternative to the potential use of wetlands in South Sumatra. Shallot as one of important crop commodities is considered to be able to adapt well to this floating systems. However, the use of inorganic chemicals should be minimized to avoid polluting the water below. Thus, this research was conducted to evaluate the effect of liquid organic fertilizer application on shallot plants grown on mixed media of cow manure in a floating system. This research was carried out at the reservoir of Agriculture Faculty of  Sriwijaya University Indralaya using a Randomized Block Design with 4 treatment levels and 3 replicates. The treatment was liquid organic fertilizer dose consisted of P0 = control (recommended dose of NPK fertilizer = 1,4 g NPK per polybag); P1 = 4 ml liquid organic fertilizer per liter; P2 = 8 ml liquid organic fertilizer per liter; P3 = 16 ml liquid organic fertilizer per liter. Parameters observed were plant length, leaf number, tiller number, leaf greenness, plant dry weight, bulb diameter, bulb fresh weight, and air-dried bulb weight. The results showed that the application of liquid organic fertilizer gave a positive effect compared to the control treatment. In general, P3 treatment was the best treatment as shown in growth and yield parameters.